2013
DOI: 10.1016/j.jconhyd.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification and indirect N2O emissions in groundwater: Hydrologic and biogeochemical influences

Abstract: Identification of specific landscape areas with high and low groundwater denitrification potential is critical for improved management of agricultural nitrogen (N) export to ground and surface waters and indirect nitrous oxide (N 2 O) emissions. Denitrification products together with concurrent hydrogeochemical properties were analysed over two years at three depths at two low (L) and two high (H) permeability agricultural sites in Ireland. Mean N 2 O-N at H sites were significantly higher than L sites, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 40 publications
0
29
1
Order By: Relevance
“…At the end of each experiment, all soil cores were prepared for physical and chemical analyses. Preincubation, at peak N 2 O and N 2 emission points and at the end of incubations, soil subsamples were taken for microbial analysis, as described by Barrett et al (2010). Soil …”
Section: Physical and Chemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of each experiment, all soil cores were prepared for physical and chemical analyses. Preincubation, at peak N 2 O and N 2 emission points and at the end of incubations, soil subsamples were taken for microbial analysis, as described by Barrett et al (2010). Soil …”
Section: Physical and Chemical Analysesmentioning
confidence: 99%
“…Siemens et al (2003) revealed that the DOC leached from some agricultural soils contributed negligibly to the denitrification process because the DOC appeared not to be bioavailable. Khalil and Richards (2010), however, postulated that dissolved organic C, oxidation-reduction potential and the substrates (C and N) load differences between the land uses could regulate the degree of denitrification capacity/potential in soils.…”
Section: Relationships Between Potential Denitrification Rates and Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) and nitrous oxide (N 2 O) are the intermediate species during denitrification process but, under a given set of favorable conditions, get rapidly transformed to nitrogen gas (N 2 ). N 2 O is often used as an indicator of denitrification occurrence (Yoshinari et al 1977;Mathiesen 1998;Jahangir et al 2013). N 2 O concentrations found in shallow ground waters were threefold higher than that in water at equilibrium with atmosphere.…”
Section: Solid-phase Denitrification Processmentioning
confidence: 99%
“…Such heterogeneity influences paddock management decisions directly (Humphreys et al, 2008;Huebsch et al, 2013). Soil quality (Wilson and Maliszewska-Kordybach, 2000) is concerned with physical (the focus of the current study), chemical and biological aspects of soil across soilscapes and, therefore, defines the capacity of agricultural soil to deliver multiple functions, such as primary productivity, nutrient cycling, water filtration (Fenton et al, 2011;Jahangir et al, 2013), habitat for biodiversity and carbon sequestration (Karlen et al, 1997;Wiebe 2003;Schulte et al, 2015). This capacity can be overextended, resulting in degradation of the system by compaction (Soane and van Ouwerkerk, 1998;Robertson, 2007) or impedance of other soil functions (Creamer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%